2022
DOI: 10.3390/su14138012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Groundwater Quality and the Main Controls on Its Hydrochemistry in a Changing Climate in Morocco (Essaouira Basin)

Abstract: Groundwater is essential for both water supply and environmental conservation, especially in semi-arid and desert areas. Managing groundwater resources requires a thorough understanding of groundwater characteristics and dynamics. The hydrogeochemical properties and evolution of groundwater in the Essaouira synclinal basin in northwest Morocco were studied in this research, with 105 water samples collected in 2009, 2017, 2018, and 2019. The Water Quality Index (WQI) and Irrigation Water Quality Index (IWQI) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The link between stable chloride and water isotopes (δ 18 O, δ 2 H) is employed to provide a reliable interest by combining chemical and isotopic data to confirm the fundamental processes governing groundwater salinity. Many previous research studies [ 15 17 , 42 ] in arid and semi-arid areas have found that groundwater salinity is mainly determined by dissolution or evaporation. Indeed, the graph shows a significant increase in Cl − concentration and δ 18 O enrichment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The link between stable chloride and water isotopes (δ 18 O, δ 2 H) is employed to provide a reliable interest by combining chemical and isotopic data to confirm the fundamental processes governing groundwater salinity. Many previous research studies [ 15 17 , 42 ] in arid and semi-arid areas have found that groundwater salinity is mainly determined by dissolution or evaporation. Indeed, the graph shows a significant increase in Cl − concentration and δ 18 O enrichment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Meskala-Ouazzi sub-basin has an average elevation of 382 m, with the lowest and the highest elevations of 4 m and 714 m, respectively. Two rivers cross the Meskala-Ouazzi sub-basin: Wadi Ouazzi and Wadi Igrounzar, whose natural outlet is the Atlantic Ocean [ 15 17 ].
Fig.
…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, there has been increased global attention towards assessing groundwater quality to ensure its suitability for various applications. Various techniques, including binary plots, ionic ratios, Wilcox plots, Piper diagrams, Schoeller diagrams, USSL diagrams, and Gibbs diagrams have been employed to evaluate the hydrogeochemical behavior of groundwater [19][20][21][22][23]. Moreover, to ascertain groundwater suitability, hydrochemical characteristics and ionic concentrations are often assessed against the standards set by the World Health Organization (WHO) [24].…”
Section: Introductionmentioning
confidence: 99%